Trade Linkages Between the Belt and Road Economies - Boffa, Mauro (World Bank, Washington, DC, 2018)
This paper studies the production and trade linkages between a selected group of economies belonging to the Belt and Road Initiative (BRI). After defining a group of Belt and Road Economies, the paper uses three standard trade databases to analyze trade and production linkages among these economies. With the help of state of the art economic decompositions of input-output tables, coupled with standard international trade statistics, the analysis quantifies the amount of production sharing between the economies of the area. The main finding is that trade integration among Belt and Road Economies has largely increased: Intraregional exports went from 30.6 percent in 1995 to 43.3 percent in 2015. Since the increase in gross exports was driven mostly by intermediate goods, the study investigates the evolution of regional production networks across Belt and Road Economies.